Correction: Error mitigation in LPWAN systems: A study on the efficacy of Hamming-coded RPW. - Muhammad Moazzam Ali; Shaiful Jahari Hashim; Zaid Ahmad; Guillaume Ferre; Fakhrul Zaman Rokhani; Muhammad Akmal Chaudhary (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0304386.].